2012
DOI: 10.1364/oe.20.021875
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of realized metal-insulator-silicon-insulator-metal waveguides and nanochannel fabrication via insulator removal

Abstract: We investigate experimentally metal-insulator-silicon-insulator-metal (MISIM) waveguides that are fabricated by using fully standard CMOS technology. They are hybrid plasmonic waveguides, and they have a feature that their insulator is replaceable with functional material. We explain a fabrication process for them and discuss fabrication results based on 8-inch silicon-on-insulator wafers. We measured the propagation characteristics of the MISIM waveguides that were actually fabricated to be connected to Si ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…On the whole, the propagation loss for w S ¼ 190 nm is smaller than that for w S ¼ 160 nm. Similar to the previous observation, 23 this is caused by the fact that the narrower the Si strip is, the more strongly the hybrid plasmonic mode is confined in the channels. As n l increases, the propagation loss decreases.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…On the whole, the propagation loss for w S ¼ 190 nm is smaller than that for w S ¼ 160 nm. Similar to the previous observation, 23 this is caused by the fact that the narrower the Si strip is, the more strongly the hybrid plasmonic mode is confined in the channels. As n l increases, the propagation loss decreases.…”
supporting
confidence: 87%
“…Metal-insulator-silicon-insulator-metal (MISIM) waveguides are such hybrid plasmonic waveguides which are realized by using standard complementary metaloxide-semiconductor (CMOS) technology. [13][14][15][16][17][18][19][20][21][22][23][24] A variety of passive MISIM waveguide devices have been realized. [18][19][20]23,24 For active MISIM waveguide devices, it was experimentally demonstrated that the phase of the MISIM waveguide mode can be tuned by depleting or accumulating electrons in the silicon strip of a MISIM waveguide.…”
mentioning
confidence: 99%
See 3 more Smart Citations